Comparative evaluation of platelet rich plasma in socket healing and bone regeneration after surgical removal of impacted mandibular third molars - Ravi Bhujbal; Neelima A Malik; Nilesh Kumar; Suresh KV; Mushtaq I Parkar; Jeevan MB (Tabriz University of Medical Sciences, 2018)
Background. Surgical removal of mandibular third molars results in pain, swelling and bony defects, causing prolonged postoperative recovery. The growth factors present in platelet-rich plasma (PRP) can accelerate the healing, thereby shortening postoperative recovery period. This study was undertaken to evaluate the role of PRP in postoperative socket healing, pain, swelling and bone regeneration following surgical removal of impacted mandibular third molars. Methods. The present case‒control study was conducted on 20 patients with identical bilateral mandibular third molar impaction. PRP was placed randomly on one side of 3rd molar extraction socket and the contralateral side was used as control. Evaluation of soft tissue healing, pain, swelling and radiologic bone density was carried out. Results. Soft tissue healing was better in the PRP compared to the control site. Immediate postoperative assessment of pain scores showed no significant difference between the two groups (Mann-Whitney U test). On the 7th day, pain scores were lower in case site compared to the control site. Measurement of swelling on the 1st, 3rd and 7th day showed statistically significant differences between the case and control sites (P<0.0001). Postoperative mean bone density at the 3rd and 6th postoperative months was significantly higher in the case site compared to the control site (P=0.00001). Conclusion. The results showed an improvement in wound healing and swelling and an increase in the bone density at PRP site. The growth factors in PRP would improve the hard and soft tissue healing 3 months after molar surgery.